Does Transformational Leadership and Flexible Working Arrangements Affect Journalist Performance? The Mediating Role of Job Satisfaction - Syaiful Rahman; Dewie Tri Wijayati; Anang Kistyanto (Journal of Business and Management Review, 2023)
The purpose of this study was to evaluate the effect of transformational leadership and flexible working arrangements on the performance of journalists through job satisfaction. Data was collected from journalists who are members of the Indonesian Journalists Association of East Java Province (PWI East Java) through a questionnaire survey that was distributed. A total of 100 completed questionnaires were received. The hypothesis was tested using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach supported by the Smart-PLS 3 computer software program. The results of the study show that transformational leadership, flexible work arrangements, and job satisfaction have a significant positive correlation with journalist performance. It was also found that job satisfaction mediates the relationship between flexible work arrangements and journalist performance. However, job satisfaction does not mediate the relationship between transformational leadership and journalist performance. This study proposes that companies need to ensure that leaders at all levels have strong transformational leadership qualities and create a work environment that can increase employee satisfaction. Companies must understand the factors that can increase job satisfaction, such as providing constructive feedback, work flexibility, and a healthy work-life balance. By increasing job satisfaction, employees will feel more satisfied with their jobs, which will ultimately have a positive impact on their performance. This kind of research has not been completed or even not discussed in academic research. Therefore, this problem needs to be included in management science.